2013
DOI: 10.1242/jeb.085753
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of sand tiger sharkCarcharias taurusvertebrae in relation to spinal deformity

Abstract: SUMMARYApproximately 35% of sand tiger sharks (Carcharias taurus) in public aquaria exhibit spinal deformities ranging from compressed vertebrae and loss of intervertebral space to dislocated spines with vertebral degeneration and massive spondylosis caused by excessive mineralization both within vertebrae and outside the notochordal sheath. To identify the mechanical basis of these deformities, vertebral centra from affected (N=12) and non-affected (N=9) C. taurus were subjected to axial compression tests on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The apparatus was placed into elasmobranch ringer's solution (Forster et al, 1972) for at least 30 min to allow the putty to set. Once set, the putty had an elastic modulus of 3.19 GPa, which is three orders of magnitude higher than the modulus of articular cartilage and about one order of magnitude higher than that of previously tested mineralized shark cartilage (Korhonen et al, 2002;Jin and Lewis, 2004;Stolz et al, 2004;Porter et al, 2006Porter et al, , 2013Macesic and Summers, 2012;Ferrara et al, 2013;Huber et al, 2013;Liu et al, 2014; Table S1). The hyomandibula was then placed in the materials testing machine so the discs were parallel with the compression platens and the hyomandibula could be loaded along the longitudinal axis (Fig.…”
Section: Compression Testingmentioning
confidence: 81%
“…The apparatus was placed into elasmobranch ringer's solution (Forster et al, 1972) for at least 30 min to allow the putty to set. Once set, the putty had an elastic modulus of 3.19 GPa, which is three orders of magnitude higher than the modulus of articular cartilage and about one order of magnitude higher than that of previously tested mineralized shark cartilage (Korhonen et al, 2002;Jin and Lewis, 2004;Stolz et al, 2004;Porter et al, 2006Porter et al, , 2013Macesic and Summers, 2012;Ferrara et al, 2013;Huber et al, 2013;Liu et al, 2014; Table S1). The hyomandibula was then placed in the materials testing machine so the discs were parallel with the compression platens and the hyomandibula could be loaded along the longitudinal axis (Fig.…”
Section: Compression Testingmentioning
confidence: 81%
“…EPMs could represent an earlier stage in the formation of the massive hypercalcifications/fusions described by Maisey (2013). Many authors have also observed pathologic, mineralized masses encasing portions of the vertebral column in sharks (Hoenig & Walsh, 1983;Huber et al, 2013;Officer et al, 1995;Porter et al, 2006), particularly in captive sandtiger sharks (Carcharias taurus) with spinal deformities (Fig. 11A), encasing sites of former vertebral fracture or dislocation (Fig.…”
Section: Epms In Contextmentioning
confidence: 98%
“…The endoskeletons of sharks and rays (elasmobranch fishes) are typically described as being composed of unmineralized cartilage and two distinct types of calcified cartilage, which differ in their location and ultrastructure. Areolar calcified cartilage is a highly cellular, net-like mineralized tissue, with the cells occupying the holes in the net, that is only found in the centra of the vertebral column (Clement, 1992;Compagno 1988;Huber et al, 2013;Porter et al, 2006). In contrast, tessellated calcified cartilage comprises the remainder and vast majority of the endoskeleton (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is applicable because many biological structures can be treated as beams (e.g. trees, echinoderms, vertebral columns; Koehl, 1977;Baumiller, 1993;Ennos, 1993;Huber et al, 2013), and beam theory also facilitates better comprehension of form and function relationships by teasing apart factors that contribute to a biological beam's performance under loading. A beam's resistance to bending is given by the flexural stiffness EI, which is a function of both its material properties (via Young's modulus, E) and its geometry (via second moment of area, I ) (Koehl, 1976(Koehl, , 1977Wainwright et al, 1976;Biewener and Full, 1992).…”
Section: Introductionmentioning
confidence: 99%